2023
DOI: 10.3389/fpsyt.2023.1205824
|View full text |Cite
|
Sign up to set email alerts
|

Differences in psychometric characteristics of outpatients with somatic symptom disorder from general hospital biomedical (neurology/gastroenterology), traditional Chinese medicine, and psychosomatic settings

Abstract: ObjectiveThe aim of this study is to investigate the psychometric characteristics of outpatients diagnosed with somatic symptom disorder (SSD) in biomedical, Traditional Chinese Medicine (TCM) and psychosomatic settings.Materials and methodsA total of 697 participants who completed SCID-5 and questionnaires were presented in our former study, as 3 of them had missed questionnaire data, a total of 694 participants are presented in this study. A secondary analysis of the psychometric characteristics of Somatic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has been shown that specificity can increase while sensitivity decreases if many of the study participants score far below the applied cut-off values ( 18 ). On the other hand, sensitivity can increase while specificity decreases if previous diagnostic investigations lead to a selection of patients with more severe symptoms ( 21 , 22 ). Our findings suggest that the spectrum effect might be large in the case of SSD when comparing psychosomatic outpatients and unselected primary care patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that specificity can increase while sensitivity decreases if many of the study participants score far below the applied cut-off values ( 18 ). On the other hand, sensitivity can increase while specificity decreases if previous diagnostic investigations lead to a selection of patients with more severe symptoms ( 21 , 22 ). Our findings suggest that the spectrum effect might be large in the case of SSD when comparing psychosomatic outpatients and unselected primary care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether combination #2 with much lower cut-offs is a good choice for primary care remains unclear. In a recent re-analysis of their data (22), Cao et al discuss a slightly higher cut-off (≥16) when applying the SSD-12 only, without the PHQ-15.…”
Section: Discussionmentioning
confidence: 99%